Control and order in French colonial Louisbourg, 1713-1758 - Johnston, A. J. B. (Andrew John Bayly) (Michigan State University Press, 2001)
"Control and Order in French Colonial Louisbourg, 1713-1758 is the culmination of nearly a quarter century of research and writing on 18th-century Louisbourg by A.J.B. Johnson. The author uses a multitude of primary archival sources - official correspondence, court records, parish registries, military records, and hundreds of maps and plans - to put together a detailed analysis of a distinctive colonial society. Located on Cape Breton Island (then known as Ile Royale), the seaport and stronghold of Louisbourg emerged as one of the most populous and important settlements in all of New France. Its economy was based on fishing and trade, and the society that developed there had little or nothing to do with the fur trade, or the seigneutial regime that characterized the Canadian interior. Johnston traces the evolution of a broad range of controlling measures that were introduced and adapted to achieve an ordered civil and military society at Louisbourg. He views the efforts to control and regulate society through the lenses of town planning, civil and religious celebration, public punishment, and the criminal justice system. A.J.B. Johnston's Control and Order in French Colonial Louisbourg, 1713-1758 offers both a broad overview of the colony's evolution across its half-century of existence, and insightful analyses of the ways in which control was integrated into the mechanisms of everyday life."--Jacket